Instilling Nationalism and Sociopreneurship in Young Indonesian Immigrants - Mutiara, Indah Ainun; Syamsuddin, Agustan; Maharida, Maharida; Napasti, Friny; Hasnawati, Lina (Pandawan, 2025)
This article explores the implementation of programs aimed at instilling the spirit of nationalism and love for the homeland in the young generation of Indonesian immigrants in the Sentul area of Kuala Lumpur, Malaysia. The urgency lies in fostering a deep understanding and appreciation of nationalism and patriotism among these young individuals, who often face challenges in accessing education due to incomplete essential documents. This study uses initial assessments through observations and interviews, collaborative educational sessions with local guidance centers, and interactive activities such as discussions, quizzes, and cultural events. Significant results show an increase in the young immigrants awareness and embodiment of national values, demonstrated by a stronger sense of identity and connection to their homeland. Tailored educational approaches that integrate Indonesia struggle for independence, national symbols, and cultural heritage play a critical role in maintaining national identity among immigrant populations. Continuous efforts are necessary to ensure that the younger generation remains connected to their heritage and develops a robust nationalistic spirit, even when living abroad.